2012
DOI: 10.1021/am301848a
|View full text |Cite
|
Sign up to set email alerts
|

Field Emission Properties of Gold Nanoparticle-Decorated ZnO Nanopillars

Abstract: The structural and optoelectronic properties of ZnO nanopillars (ZnO-NPs) grown on Si substrates by the vapor transport deposition method were investigated. In particular, by varying the deposition duration and hence the morphology of the vertically aligned ZnO-NPs, the resultant field emission characteristics were systematically compared. In addition to identifying the advantageous field emission properties exhibited in the pencil-like ZnO-NPs, we observed that by adhering Au nanoparticles on the surface of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 55 publications
0
54
1
Order By: Relevance
“…Since the work function of CuO (2.5 eV) is smaller than that of Au (5.1 eV), a better ohmic contact can be generated between CuO and Au. The electron transport channel will be amplified by the coating of Au nanoparticles [28]. As a result, the field emission properties were enhanced greatly by decorating Au nanoparticles on the CuO nanoplate arrays.…”
Section: Resultsmentioning
confidence: 99%
“…Since the work function of CuO (2.5 eV) is smaller than that of Au (5.1 eV), a better ohmic contact can be generated between CuO and Au. The electron transport channel will be amplified by the coating of Au nanoparticles [28]. As a result, the field emission properties were enhanced greatly by decorating Au nanoparticles on the CuO nanoplate arrays.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to measure local variations in charge density, electric field, and electrostatic potential in nanoscale materials and devices, such as doped semiconductors [1][2][3][4] and nanoscale field emitters, [5][6][7][8] in the transmission electron microscope (TEM) is important for understanding the relationship between internal microstructure, chemistry, defects, and functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Sugavaneshwar et al 34 have reported an enhancement in the eld emission of branched ZnO nanostructures compared to that of simpler nanostructures such as nanowires and nanorods, etc., but the actual values of E on were not stated. Although Chang et al 27 have reported an enhancement in the FE properties of ZnO nanopillars aer decorating Au nanoparticles along the surface, the minimum E on of the ZnO nanopillars which was limited to 3.15 V mm À1 was further reduced to 2.65 V mm À1 (aer Au decoration) owing to the larger diameter and at top of the ZnO nanopillars (i.e. $200 nm).…”
Section: Resultsmentioning
confidence: 96%
“…an average of AE5%) was observed even aer continuous emission for 180 min. These spitzer shaped 1D ZnO nanowires exhibited very stable and improved electron emission than that of gold nanoparticle decorated ZnO nanopillars, 27 monolayer graphene supported by well-aligned ZnO nanowire arrays grown on Si substrates, 44 seed layer assisted ZnO nanorods, 45 ZnO nanowires derived aer annealing gold deposited Zn substrate at 400 C, 46 and ZnO multipods, submicron wires and spherical structures obtained by vapour deposition. 47 The exclusive participation of the sharp tips of the ZnO nanowires as emitters conceivably enhanced the emission ability.…”
mentioning
confidence: 99%